The oil palm Agribusiness in Colombia [2017] - Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma (Federación Nacional de Cultivadores de Palma de Aceite, 2020)
Colombia ranks top in America and fourth in the world as producer of palm and palm kernel oil. Oil palm crops are among the most promising agricultural activities as drivers of national development.
Keywords: Agroindustria; Aceite de palma; Colombia; Cenipalma; Agremiación